Structural insights into the critical DNA damage sensors DNA-PKcs, ATM and ATR. (October 2019) - Baretic, Domagoj; Maia de Oliveira, Taiana; Niess, Martina; Wan, Paul; Pollard, Hannah; Johnson, Christopher M.; Truman, Caroline; McCall, Eileen; Fisher, David; Williams, Roger; Phillips, Christopher
Abstract: ATM, ATR and DNA-PKCs are key effectors of DNA Damage response and have been extensively linked to tumourigenesis and survival of cancer cells after radio/chemotherapy. Despite numerous efforts, the structures of these proteins remained elusive until very recently. The resolution revolution in Cryo-EM allowed for molecular details of these proteins to be seen for the first time. Here we provide a comprehensive review of the structures of ATM, ATR and DNA-PKcs and their complexes and expand with observations springing from our own cryo-EM studies. These observations include a novel conformation of ATR and novel dimeric arrangements of DNA-PKcs.